E-056 Pipeline Endovascular Device for the Treatment of Intracranial Aneurysm at the Level of the Circle of Willis and Beyond: Multicenter Experience. (26th July 2014) - Martínez-Galdámez, M; Linfante, I; Lin, E; Dabus, G
Abstract : Background and purpose: The aim of our study was to evaluate the safety and eficacy of the Pipeline endovascular device for the treatment of anterior circulation aneurysms at the level of circle of Willis and beyond. Methods: A consecutive series of 23 patients with unruptured and 1 with ruptured anterior circulation aneurysms treated with Pipeline endovascular device. Complication rates, aneurysm obliteration, modified Rankin Scale (mRS) outcomes were assessed. Results: All devices were placed properly, without technical difficulties. We found 1 minor clinical event (resolved within 7 days from procedure) and 1 major event (symptoms present after 7 days) (table), and no mortality. There were no aneurysm rupture or parenchymal haemorrhage during follow-up. The mRS at 3 and 6 months did not change from prior mRS in all cases but 1. We had 2 asymptomatic periprocedural ischemic events: 1 perforator stroke in the case of a recanalised A1-A2 where we used 2 PEDs, and 1 lacunar stroke. Both cases were discovered incidentally at the control CT predischarge. We had 3 intraprocedural complications, resolved without clinical consequences:1 acute branch occlusion during hypotension state which was solved after TA raise (case 4), 1 slow opacification of the inferior trunk of MCA resolved with intraarterial bolus of reopro (case 20), and 1 focal SAH secondary to distal perforation with the microwire during and exchange manoeuvre which was resolved with coil occlusion and glue at the level of the perforation, with no symptoms (case 14) Six-month follow-up angiograms were obtained in 16 aneurysms, showing complete occlusion in 9 and significantly decreased residual filling in 7. 5 cases are still pending on 6 months DSA and 1 case showed residual filling at the 3 months follow-up. Patency of PEDs and status of branches originating from the aneurysm sacs were evaluated in 17 and 11 angiograms respectively. All PEDs were patent, but we found 4 intrastent stenosis at 6 months DSA where only 1 symptomatic case (an angioplasty was done successfully). In the 11 branches evaluated, 7 were patent, 2 moderate reduced and in 2 cases were occluded asymptomatically. Conclusion: The PED provides a safe and effective solution for aneurysms at and beyond the circle of Willis. Preliminary results are promising but larger series with longer-term follow-up examinations are required to show the long-term safety and durability of this treatment alternative. Disclosures: M. Martínez-Galdámez: 2; C; Covidien. I. Linfante: 2; C; Covidien, Stryker, Codman. E. Lin: None. G. Dabus: 2; C; Covidien, Microvention, Reverse Medical.